Mobile Learning and Student Motivation: A Meta Analytic Comparison of Global and Indonesian Evidence - Mariana, Rina Rifqie; Nurjanah, Nunung (Eduscape : Journal of Education Insight, 2025)
Synthesizing Global and Indonesian Evidence on Mobile Learning and Student Motivation: A Meta Analytic Approach This study synthesizes evidence from 24 empirical studies (2010–2025) to examine the effect of mobile learning on student motivation. Using systematic review procedures (PRISMA 2020), the analysis compares global and Indonesian findings. The study includes RCTs and quasi-experiments across K-12 and higher education, focusing on student motivation measured by validated instruments. The methodology involved comprehensive searches across international (Scopus, ERIC, PubMed, ProQuest, DOAJ) and Indonesian (Garuda, SINTA) databases, followed by strict application of inclusion criteria aligned with the PICOS framework. Effect sizes were computed using Hedges’ g, with corrections for small sample bias. Moderator analyses explored the influence of app features (gamification, AR, adaptivity), educational level, regional context, and measurement instruments on motivational outcomes. Results show that mobile learning has a positive effect on student motivation, with stronger effects observed in Indonesian studies. Applications that feature adaptive learning, gamification, or AR yield greater motivational benefits. The findings are consistent across studies, suggesting robust evidence for the positive role of mobile learning. These findings are discussed within Self-Determination Theory and the ARCS model, highlighting the importance of culturally responsive and participatory design. The study acknowledges methodological limitations and suggests practical directions for inclusive and scalable mobile learning. The study concludes by advocating for scalable, inclusive mobile learning solutions that integrate motivational frameworks and cultural adaptability.